2019
DOI: 10.1039/c9py00113a
|View full text |Cite
|
Sign up to set email alerts
|

Bromoalkyl ATRP initiator activation by inorganic salts: experiments and computations

Abstract: The bromoalkyl ATRP initiator EBrPA is activated by many alkali, alkaline-earth and ammonium salts, leading to MMA polymerization, but only the iodides yield a controlled process because of a degenerative transfer mechanism contribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 70 publications
(88 reference statements)
2
23
0
Order By: Relevance
“…This agrees with the greater efficiency of KOH as activator for EBrPA relative to KBr. 32 In addition, the same two peaks already observed in the EBrPA/FeBr3/KOH experiment ( Figure S15) at 16.00 and 26.11 min are also observed here. Finally, this GC trace also reveals a very small peak at 11.26 min, the identity of which as methyl 1,2-dibromoisobutyrate was confirmed by the MS, see Figure S18(b).…”
Section: (E) Mechanistic Studiessupporting
confidence: 84%
See 4 more Smart Citations
“…This agrees with the greater efficiency of KOH as activator for EBrPA relative to KBr. 32 In addition, the same two peaks already observed in the EBrPA/FeBr3/KOH experiment ( Figure S15) at 16.00 and 26.11 min are also observed here. Finally, this GC trace also reveals a very small peak at 11.26 min, the identity of which as methyl 1,2-dibromoisobutyrate was confirmed by the MS, see Figure S18(b).…”
Section: (E) Mechanistic Studiessupporting
confidence: 84%
“…Hence, FeBr3 must be converted to the FeBr2 activator by another reduction mechanism, followed by a regular ATRP with FeBr2/EBrPA as activator/initiator pair, as demonstrated in numerous previous contributions. 33 In a recent study, 32 we have shown how inorganic salts (Mt + X -), including alkali metal carbonates and halides, are able to activate EBrPA in the absence of iron complexes to initiate the MMA radical polymerisation, although in an uncontrolled manner. This occurs by atom transfer with formation of the EPA radical and the Mt + (BrX • )radical adduct.…”
Section: (E) Mechanistic Studiesmentioning
confidence: 99%
See 3 more Smart Citations